Angiosperms additions to flora of Peru - Rodríguez, Eric F. (2006)
We present here 131 new additions to the angiosperm flora of Peru from recent collections in the north of Peru, mostly from department of Amazonas (provinces of Bagua and Condorcanqui) and department of Cajamarca (province of San Ignacio). This new contribution is the result of field and herbarium studies by the various authors in this region from 1993 to 2002, and represents the combined effort of personnel from the Herbarium Truxillense (HUT) and the Herbarium of the Missouri Botanical Garden (MO) as part of the Flora of Peru Project. The species reported here were compared against the list of species documented in the «Catalogue of Flowering Plants and Gymnosperms of Peru» (Brako & Zarucchi, 1993) and «Ten years of additions to the flora of Peru: 1993- 2003» (Ulloa Ulloa et al., 2004). The new taxa are organized in three categories: 18 species new to science, six new nomenclatural combinations and 107 new records, thereby enlarging their geographical distribution towards to Peru. Considering the new species and the new records, this contribution adds 125 species to the Peruvian Flora.